Peranan Badan Penyelesaian Sengketa Konsumen (BPSK) Kota Banjarmasin - Hardianto Hardianto (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
Consumer Dispute Settlement Board is a Board / Independent Institute, a public body which has the role, duties and responsibilities include implementing and penyelesaianan handling consumer disputes Conciliation, Mediation and Arbitration, provide consumer protection consultation, to supervise the inclusion of standard clauses, reported to general investigators, receive complaints both written and unwritten, calling businesses are alleged to have committed a violation, call and produce witnesses and administrativ sanctions against businesses that violate. The method used in this study is a qualitative approach, to determine the source of the data used purposive sampling technique. Data was collected through observation, semi-structured interviews, and dokomentasi. Data analysis was done by reducing the data, presentation of data, and draw conclusions.The results showed (1) the role of BPSK in resolving consumer disputes out of Court by using the method of settlement in mediation, conciliation and arbitration. Disputes that go on in 2012/2014 to BPSK Banjarmasin as many as 31 cases, mediation settlement form more among others, namely 11 cases. (2) Law BPSK decision against the perpetrators to the dispute in accordance with the result of collective deliberation or decision of the panel BPSK binding and ends, and can’t be contested or appealed.Based on these results, it can be suggested that the presence of BPSK terkaitt for this community Banjarmasin not too familiar with BPSK. BPSK should socialize more about where BPSK in Banjarmasin. Every community and consumers as connoisseurs, user and / users of goods and / services can complain and disappointment to the goods / services to BPSK, before the State to court.Keywords: role, consumer dispute resolution